2006
DOI: 10.1093/jxb/erl086
|View full text |Cite
|
Sign up to set email alerts
|

Gene profiling of the red light signalling pathways in roots

Abstract: Red light, acting through the phytochromes, controls numerous aspects of plant development. Many of the signal transduction elements downstream of the phytochromes have been identified in the aerial portions of the plant; however, very few elements in red-light signalling have been identified specifically for roots. Gene profiling studies using microarrays and quantitative Real-Time PCR were performed to characterize gene expression changes in roots of Arabidopsis seedlings exposed to 1 h of red light. Several… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
41
1
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 88 publications
1
41
1
2
Order By: Relevance
“…The authors showed that the small amount of light that passes through the soil is sufficient to repress AS1 expression in roots. Furthermore, recent microarray experiments identified several genes differentially expressed in roots of dark-grown Arabidopsis seedlings exposed for 1 h to red light (Molas et al, 2006). In agreement with the hypothesis of a direct action of light in roots, three classes of light receptors have been found in Arabidopsis roots: the phytochromes, the cryptochromes, and phototropin (Neff et al, 2000;Quail, 2002).…”
Section: Regulation Of Root Ion Transporters Bymentioning
confidence: 62%
“…The authors showed that the small amount of light that passes through the soil is sufficient to repress AS1 expression in roots. Furthermore, recent microarray experiments identified several genes differentially expressed in roots of dark-grown Arabidopsis seedlings exposed for 1 h to red light (Molas et al, 2006). In agreement with the hypothesis of a direct action of light in roots, three classes of light receptors have been found in Arabidopsis roots: the phytochromes, the cryptochromes, and phototropin (Neff et al, 2000;Quail, 2002).…”
Section: Regulation Of Root Ion Transporters Bymentioning
confidence: 62%
“…For example, R light absorbed by rootlocalized phyA and phyB impacts root phototropism (Kiss et al, 2003) and inhibits root elongation rates (Correll and Kiss, 2005) in Arabidopsis. Recent microarray analyses for roots exposed to R light indicate that the expression of many genes, including a number of genes involved in photomorphogenesis and root development, are regulated by light in roots (Molas et al, 2006). FR light also impacts root growth, i.e.…”
mentioning
confidence: 99%
“…27 In addition, in maize roots, the xylem water flux sustained by root pressure occurs during the day and is less important at night. 28 More generally, gene profiling of the red light signaling pathways in Arabidopsis roots performed by Molas et al 29 allowed the identification of several factors acting downstream of phytochromes in red-light signaling among which genes involved in lateral root and root hair formation, root plastid development, hormone signaling and phenylpropanoid metabolism.…”
Section: Possible Function Of Ntann12 In Shoot To Root Signalingmentioning
confidence: 99%